From the Ashes - Boswall, Karen ((n/a), 1999)
Soros Documentary Fund Volume one of "Landscape of Memory," a four part documentary series on reconciliation in Southern Africa, "From the Ashes" focuses on Mozambique. This film gives the viewer the possibility to grasp the traditional approach to reconciliation in Mozambique following the sixteen year civil war which ended in 1992. It is set in a small village in the south of Mozambique, Ilha Josina, and follows people who fought on both sides of the war and suffered at the hands of both. The film shows how, through ritual, spiritual beliefs and personally developed philosophies, the villagers are reconciling their past, living the present and working towards their futures.